Win-win upcycling strategy for red araçá fruit waste: Process intensification and application of food-grade cyanidin-rich antioxidants - Angie V. Caicedo-Paz; Henua U. Hucke; Alessia Tropea; Luigi Mondello; Cassamo U. Mussagy (Future Foods)
The valorization of non-marketable red araçá fruit represents a crucial step toward achieving circular economy goals, tackling agrifood waste while advancing sustainable practices. Large amounts of these fruits are discarded due to not meeting commercial standards, resulting in significant environmental and economic losses. However, these discarded fruits hold untapped biological potential, particularly for the food industry. This study optimized microwave-assisted extraction (MAE) to recover cyanidin-rich pigments from red araçá. The MAE method demonstrated high efficiency, yielding extracts with concentrations ranging from 3.5 mg/mL to 4 mg/mL under optimal conditions (300 W for 120 s). The pigments exhibited a significant 100% radical scavenging activity in DPPH assays and maintained color stability for 18 days when incorporated into natural yogurt. Sensory evaluations revealed strong consumer acceptance, with participants favoring formulations with 0.35 µgcyanidin/gyogurt. These results underscore the potential of cyanidin-rich pigments to enhance food quality and stability, showcasing their role in advancing sustainable resource utilization within the food industry. In fact, this research highlights the importance of red araçá valorization as a sustainable resource, driving a circular economy through innovative extraction processes and their practical applications in the food industry.